Congenital melanocytic nevus/Plexiform neurofibroma. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2012)
Plexiform neurofibroma is the earliest cutaneous neoformation of peripheral neurofibromatosis. As it is frequently associated with hypertrichosis and hyperpigmented epidermis, plexiform neurofibroma should be differentiated from congenital melanocytic nevus.